Digitization of Cylindrical GEM Detector. (April 2020) - Zhao, Jingyi; Miao, Nannan; Wu, Linghui; Wang, Liangliang; Sun, Tong; Huang, Zhen; Mitchell, Ryan; Li, Weiguo; Liu, Huaimin; Lou, Xinchou; Sun, Shengsen; Yuan, Ye; et al.
Abstract: The BESIII inner drift chamber is suffering from aging effect. Cylindrical Gas Electron Multiplier Inner Tracker (CGEM-IT) is considered as one of the upgrade candidates. A simulation study with Garfield++ program has been performed to understand the drift behaviour and to build a full digitization model. Parameters related to Lorentz angle, diffusion effect, drift time, multiplication and induction are obtained from the Garfield++ simulation. A preliminary digitization model is implemented in the BESIII Offline Software System (BOSS) based on those parameters.